Preservation of Kejek Tea as a Gastronomic Legacy of Garut Regency - Hamidah, Sarah Nur; Turgarini, Dewi; Handyastuti, Indriyani (Universitas Pendidikan Indonesia, 2019)
Kejek tea is a traditional Cigedug tea. The purpose of this research is to know the existence, how to make tea in a traditional way, how to drink Kejek Tea and describe the tea Keek into a gastronomic tourist attraction in Garut Regency. The research method used is a descriptive qualitative research. The method for obtaining data is by conducting in-depth interviews, observation and documentation. Cigedug Village, Garut as a place to do research activities. The results of this study can be seen that: (1) Kejek tea has existed since the Dutch era in the 1900s. (2) How to manufacture that is still done manually using foot power and traditional tools. (3) Kejek Tea has a tradition of drinking tea, namely Nyaneut Tradition. (4) Kejek Tea has the potential is high enough to be a product that can increase income for the surrounding community if it is able to be developed or managed properly. Efforts to preserve traditional tea must be done not only by producers, the government but must also involve all elements of society.